EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS ASSISTED INDIVIDUALIZATION (TAI) YANG DILENGKAPI ASSESMENT FOR LEARNING PADA POKOK BAHASAN BANGUN DATAR DITINJAU DARI GAYA KOGNITIF SISWA KELAS VII SMP N SE-SURAKARTA TAHUN PELAJARAN 2013/2014 - Arief Kristyawan; Budiyono Budiyono; Gatut Iswahyudi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of this study were to determine: (1) among the cooperative learning model TAI type equipped AfL, TAI or direct learning equipped AfL that provide better learning achievement. (2) among students who have cognitive style type of field dependent or fields independent that provided better learning achievement. (3) on each of students group with cognitive style type (field dependent or field independent), which learning models that provide better learning achievement. (4) on each of learning model (cooperative learning model of TAI type equipped AfL, TAI or direct learning equipped AfL), which cognitive styles that provide better learning achievement. This research was quasi-experimental research. The population was all of seventh grade students of State Junior High School in Surakarta in academic year of 2013/2014. The research samples ware 302 students, taken used a stratified cluster random sampling technique. The data collection instruments used ware learning achievement test and cognitive style test. Hypothesis testing used unbalanced two ways analysis of variance. The research conclusions are as follows.  (1) The TAI learning model equipped AfL provides better learning achievement than TAI learning model and direct learning equipped AfL, while TAI learning model provides better learning achievement than direct learning model equipped AfL. (2) Students with cognitive style of field independent have better learning achievement than students with field dependent. (3) In the cognitive style of field dependent and field independent, TAI learning models equipped AfL provides better learning achievement than TAI learning model and direct learning model equipped AfL, while TAI learning model provides a better learning achievement than direct learning model equipped AfL. (4) In the TAI learning model equipped AfL, TAI and direct learning model equipped AfL, the students group with cognitive styles of field independent have better learning achievement than students with field dependent.  Keywords: TAI, AfL, Cognitive Style, and Learning Achievement.